Relações lineares entre produtividade de grãos, caracteres nutricionais proteicos e variáveis meteorológicas em bases genéticas de milho - Loro, Murilo Vieira (2025)
The objectives of this study were to evaluate whether there is variability in the nutritional protein composition of grains between maize genetic bases (single hybrids, triple hybrids, double hybrids and varieties) and sowing dates; develop models to predict total and digestible amino acids for swine and poultry based on crude protein and meteorological variables; and verify whether there are linear relationships between grain yield, crude protein and meteorological variables in maize genetic bases. The experiments were carried out in the area of the Departamento de Fitotecnia at the Federal University of Santa Maria. In the 2021/2022 harvest, 78 maize genotypes were evaluated on five sowing dates: September 21, 2021, October 20, 2021, November 20, 2021, December 20, 2021 and January 30, 2022 from different genetic bases. In the 2022/2023 harvest, the same 78 maize genotypes were evaluated on five sowing dates: September 6, 2022, October 14, 2022, November 24, 2022, December 30, 2022 and February 6, 2023. In each plot, grain yield (Mg ha-1) was evaluated with moisture corrected for 13%. Using Near Infrared Reflectance Spectroscopy, 773 grain samples from the four genetic bases of maize cultivated on ten sowing dates were evaluated. Thus, for each sample, the total and digestible levels for swine and poultry of the following protein nutritional traits were determined in g/100 g of dry matter: crude protein, lysine, methionine, cystine, threonine, tryptophan, valine, isoleucine, leucine, phenylalanine, histidine and arginine. For each genotype at each sowing date, the meteorological variables were obtained: accumulated global solar radiation from sowing to female flowering (MJ m-2) and from female flowering to harvest (MJ m-2), thermal sum from sowing to female flowering (°C day) and from female flowering to harvest (°C day) and the accumulated rainfall from sowing to female flowering (mm) and from female flowering to harvest (mm). Descriptive statistics were calculated, boxplots and histograms were constructed, principal component analyses, correlation, path analysis, simple and multiple linear regression were performed. There is variation in the total and digestible levels of amino acids in grains between maize genetic bases and sowing dates. Maize varieties have the highest total and digestible amino acid content in the grains, compared to simple hybrids, triple hybrids and double hybrids, regardless of the sowing date. Sowings carried out in October and November exhibit higher total and digestible levels of amino acids in maize grains, in relation to sowings in September, December, January and February, regardless of the genetic basis. The total and digestible contents of methionine, cystine, threonine, valine, isoleucine, leucine, phenylalanine, histidine and arginine in maize grains can be predicted from crude protein with high accuracy, on all genetic bases. There are linear relationships between grain yield, crude protein and meteorological variables in maize genetic bases. There is a negative linear association between grain yield and crude protein. The global solar radiation accumulated from sowing to female flowering has a positive linear relationship with crude protein content.